The Occurrence of Sexual Risk Behaviors and Its Association With Psychological Well-Being Among Kenyan Adolescents - Ssewanyana, Derrick; Abubakar, Amina; Mabrouk, Adam; Kagonya, Vincent A.; Nasambu, Carophine; Dzombo, Judith Tumaini; Angwenyi, Vibian; Kabue, Margaret; Scerif, Gaia; Newton, Charles R. (Frontiers in Reproductive Health, 2021)
Objective: Sexual risk behavior during adolescence is an important public health problem. Self-esteem and hopefulness are potentially important psychological factors that may play a role in the behavioral regulation mechanisms of adolescents. These factors are inadequately explored in sub-Saharan Africa. This study aimed at exploring patterns and associated factors for sexual risk behavior (SRB), self-esteem, and hopefulness among adolescents from a resource-poor setting in Kenya. Method: A cross-sectional study conducted in 2019 among 296 adolescents (12–17 years old) from rural Kilifi (n = 133) and urban informal settings of Nairobi (n = 163) in Kenya. Participants completed the Kilifi Health Risk Behavior Questionnaire, Rosenberg self-esteem questionnaire, and Hope scale administered via computerized tablets. A binary outcome variable based on the experience of adolescents of at least one of the five forms of SRB: transactional sex, sexual violence, intergenerational sex, early sexual debut, and condom non-use was generated. Bi-variate analysis was conducted to summarize various social-demographic and psychosocial factors. A multivariable logistic regression model was fitted to investigate factors associated with the occurrence of SRB, self-esteem, and hopefulness among adolescents. Results: About 13% of the participants had experienced a form of SRB, and among these, 36% reported co-occurrence of multiple forms of SRB. Adolescent SRB was largely characterized by having experienced sexual violence, as well as intergenerational and transactional sex. Higher scores of hopefulness were reported among adolescents who never experienced SRB (P = 0.03) at bivariate analysis level. However, both self-esteem and hopefulness were not significantly associated with the occurrence of SRB in the adjusted logistic regression analysis. Having depressive symptoms (Adj. OR = 3.8, 95% CI: 1.39–10.4), feeling unsafe in the neighborhood (Adj. OR = 3.4, 95% CI: 1.6–7.2), and being in higher compared with lower primary education level (Adj. OR = 0.3, 95% CI: 0.1–0.8) were statistically significantly associated with the occurrence of SRB. Conclusion: Targeted reproductive health interventions, designed with the cognizance of structural and social drivers of adolescent SRB, are needed to concurrently tackle multiple forms of SRB. It is important to integrate mental health promotion within these interventions. More research is needed to understand the mechanisms and implications of self-esteem and hopefulness for adolescent sexual and reproductive health.